Optimized formulation and processing protocol for a supplementary bean-based composite flour - Ndagire, Catherine T.; Muyonga, John H.; Manju, Reddy; Nakimbugwe, Dorothy (Food Science & Nutrition, 2015)
Protein-energy malnutrition is the most serious nutritional body depletion disorder among infants and young children in developing countries, attributable to inadequate energy and nutrient intake, partly due to high dietary bulk of weaning and infant foods. The gruels fed to children are typically of low nutrient and energy density due to the low flour incorporation rate required for drinking viscosity. The aim of this study was to develop a nutritious product, based on common dry beans and other grains, suitable for supplementary feeding. The optimal processing conditions for desired nutritional and sensory attributes were determined using Response Surface Methodology. For bean processing, soaking for 6, 15, or 24 h, germination for 24 or 48 h, and cooking under pressure for either 10 or 20 min were the independent variables. The processed bean flour’s total polyphenol, phytic acid and protein content, the sensory acceptability of the bean-based composite porridge and its protein and starch digestibility were dependent variables. Based on product acceptability, antinutrients and protein content, as well as on protein and starch digestibility, the optimum processing conditions for the bean flour for infant and young child feeding were 24 h of soaking, 48 h of malting, and 19 min of steaming under pressure. These conditions resulted in a product with the highest desirability. The model equations developed can be used for predicting the quality of the bean flour and the bean-based composite porridge. Bean optimally processed and incorporated with grain amaranth and rice flours of a ratio of 40: 30: 30, respectively, resulted into flour with high energy, mineral, and nutrient density of the final porridge. The composite is well adaptable to preparation at rural community level. The use of these locally available grains and feasible processes could make a great contribution to nutrition security in sub-Saharan Africa and other developing countries.
Keywords: Antinutrients; common beans; digestibility; Response Surface Methodology; supplementary food